The Outbreak of Hepatitis A: Evidence in Pacitan District - Ratih Lukmitarani; Mufiadzatul Ardiyah; R Azizah (Universitas Airlangga, 2021)
Introduction: Indonesia is a country with a high geographical distribution of hepatitis A. In June 2019, the government established the status of hepatitis A outbreaks in Pacitan District, which is spread across several districts. Based on data from the District Health Office of Pacitan, there were 1,310 peoples with hepatitis A on October 2019. Through this study, the relation between knowledge, attitudes, and personal hygiene as risk factors of hepatitis A outbreaks in Pacitan District can be identified. Methods: Observational analytic methods and case control research design were used in this study. The population was 280 people. The sample consisted of 60 peoples with case of 30 peoples and control of 30 peoples. Case and control samples were taken randomly (simple random sampling). The research data were collected using the interview method, then analyzed using the Chi Square test and the Contingency Coefficient. Results and Discussion: There was a correlation between knowledge level with the occurrence of hepatitis A outbreaks (p-value = 0.002 <0.05), attitudes with hepatitis A (pvalue = 0.004 <0.05), and personal hygiene with the occurrence of hepatitis A outbreaks (pvalue = 0.001 <0.05). Conclusion: Inadequate knowledge, inappropriate personal hygiene lead to the spread of hepatitis A outbreaks in the working area of Primary Health Care of Ngadirojo, Pacitan District.